2017
DOI: 10.1016/j.ijmecsci.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental investigation on the residual stresses in a laser beam welded dual phase DP600 steel plate: Thermo-mechanical material plasticity model

Abstract: International audienceA thermo-mechanical plasticity material model, which consists of a hardening and a temperature sensitivity term, is built to describe the dual phase DP600 steel behavior. For the hardening term, a synthesis Ludwik–Voce hardening law is proposed, identified and compared with the classical Ludwik and the Voce hardening laws. For the temperature sensitivity function, a new proposed expression together with a classical Johnson–Cook term and an improved Chen term are analyzed and identified. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…In the structural integrity evaluation, fatigue failure becomes one of the dominant concerns. Existing studies have revealed that there are mainly three factors impacting the fatigue property of welded joints: (a) the welding residual stresses, (b) local plastic deformation resulting from the welding process, and (c) the interaction between residual stresses and fatigue damage during cyclic loadings. Some approaches have been proposed to address one or two influencing factors .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the structural integrity evaluation, fatigue failure becomes one of the dominant concerns. Existing studies have revealed that there are mainly three factors impacting the fatigue property of welded joints: (a) the welding residual stresses, (b) local plastic deformation resulting from the welding process, and (c) the interaction between residual stresses and fatigue damage during cyclic loadings. Some approaches have been proposed to address one or two influencing factors .…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation methods have the advantage of reconstructing the field of the entire structure through the actual welding progress. Finite element (FE) methods have become an effective approach in the approximate analysis of welding residual stresses . Lee et al proposed an FE evaluation to calculate the weld‐induced residual stresses and took into account a solid‐state phase transformation in carbon steel during the calculation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations